Redução de desperdícios em uma cozinha industrial por meio das ferramentas da Engenharia de Produção - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
This paper explores the application of the Production Engineering usual tools - Kaizen, Analysis and QC Story, Ishikawa, Pareto, five whys - against food waste in an industrial kitchen, with the objective of developing a protocol for implementing these tools and so contribute with suggestions to actions that could be adopted in the different existing kitchens. To this end, it was adopted the kind of research and Case Study, with an experimental approach, where the main scope is the production chain of meals in aprofessional kitchen, from the receiving points till the production process and the production delivery, limiting themselves to the environment and process of cooking. The conduct of the study was based on the Technical Regulation of Practices for Food Services of the National Health Surveillance Agency (ANVISA), since all internal actions must be conform to a Brazilian standard of food safety. The study environmentalist in a manufacturing company which supply collective meals and reach a volume with more than 4000 per day, and it is considered large and ideal for applying tools against waste scale. The research concluded that it is possible and advantageous to adopt Manufacturing Engineering Tools in the production process of industrial kitchens to reduce food waste.
Keywords: Desperdícios de alimentos; Cozinhas Industriais; Engenharia de Produção.; Food waste; Industrial Kitchens; Manufacturing Engineering.; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO